Rice Balance Simulation in Order To Support Sustainable Rice Self-Sufficiency Program in North Sumatera - Santoso, Agung Budi; Aryati, Vivi (School of Business, Bogor Agricultural University (SB-IPB), 2022)
The UPSUS program for food self-sufficiency launched by the government has succeeded in increasing national rice production, including in North Sumatera, by increasing the additional embedded area (LTT). However, the aspect of rice supply and distribution is still a problem, so rice imports are still carried out. This study aims to determine the rice balance by comparing the value of rice production to consumption every month throughout the year. The method used is a dynamic system approach using secondary data to build a simulation model. The simulation results show that, in general, the demand for rice has been fulfilled, although in certain months there is a deficit because the planting area in that month is not as large as in other months. Likewise, for some rice production centers, there are regions that experience rice deficits throughout the year. Therefore, efforts to improve supply chain management are an alternative solution to supporting sustainable rice self-sufficiency in North Sumatera. Keywords: simulation, balance, rice, self-sufficiency, sustainability